If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+3)-2=2x+2(3+x)
We simplify the equation to the form, which is simple to understand
4(x+3)-2=2x+2(3+x)
Reorder the terms in parentheses
+(+4x+12)-2=2x+2*(3+x)
Remove unnecessary parentheses
+4x+12-2=+2x+2+*(+3+x+)
Reorder the terms in parentheses
+4x+12-2=2x+(+6+2x)
Remove unnecessary parentheses
+4x+12-2=+2x+6+2x
We move all terms containing x to the left and all other terms to the right.
+4x-2x-2x=+6-12+2
We simplify left and right side of the equation.
0x=-4
0=-4
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| r-4.7=-2.5 | | n+2n+5=20 | | 2x-7=9x(8) | | (5x+9)=(7x+3) | | ln(7x+14)=2 | | 6-6x-4=44+4-14 | | (5x-1)=x | | (3x-4)=(x+6) | | 4x-2(1-x)=2(3x-1) | | 4(x-2)=y-40 | | 4(x-2)=-40 | | (x-2)(x-2)(x-2)(x-2)=-40 | | .2y-1=9 | | -0.5m-8=8 | | 7x+3+90+x=180 | | 3z^2+30z+27=0 | | x^4-40=0 | | 45x^3-36x^2+9x=0 | | 45x^3+36x^2+9x=0 | | -5(x-6)-(4+2x)=-8x | | z+6+5z-1+90=180 | | ln(5x-7)=ln(8x)-ln(2) | | ((x+3)*2)(x-1)=66 | | ((x+3)*2)(x-1)=0 | | -x+7=10 | | 8w-4-3w+9=6 | | 2x+x=x+40 | | (r-3)(r-2)=0 | | (x^2+3x+3x+9)(x-1)=66 | | -2y-1=5 | | (x+3)(x+3)*(x-1)=66 | | -11w-2=9 |